ANALISIS PENELUSURAN TRANSACTION FRAUD DALAM PEREKAYASAAN PELAPORAN KEUANGAN - Hernawan, Hernawan (Fakultas Ekonomi dan Bisnis, UNTAN, 2010)
Abstract Globalization has resulted in remarkable changes in all aspects of life, including in managing firm’s financial transaction in corporate sector. Financial reporting reengineering in large private company frequently brings about financial fraudaulous practices. The objective of this article is to shed light on fraudaulous transaction in financial reporting reengineering, which was commonly observed in private companies. Reengineered financial reporting containing transaction fraud has widely been practiced in private companies in form of increasing fantastic profits, hiding out debts, reporting ficticious incomes, cutting taxes and increasing ficticious cash flows, while it is most probable these companies have been gone bankcruptcy. Financial reporting engineering manipulation is aimed at making up with favourable financial performance of the firm in order that firm’s stocks remains attractive for investors. Keywords: fradaulous transaction, financial reporting engineering, private companies